Bleomycin: A worthy alternative - Gursev Sandlas; Paras Kothari; Parag Karkera; Abhaya Gupta (Indian Journal of Plastic Surgery)
Context: Lymphangiomas are developmental anomalies presenting mainly in the first two years of life. Surgical excision has been the mainstay of treatment; however a potentially disfiguring surgery along with presence of important structures in the vicinity and infiltration into surrounding structures makes the dissection difficult. Aims: To study the safety and efficacy of Bleomycin as a sclerosing agent for lymphatic malformations in children. Settings and Design: Prospective non comparative nonrandomized trial. Materials and Methods: The study was carried out in 15 children between Day 5 of life to 12 years of age who presented between May2008 to May 2009. Bleomycin aqueous solution was injected intralesionally at a dose not exceeding 0.6 to 0.8 mg. /kg Body wt. The response to therapy was monitored clinically by measuring the length, breadth and area as well as by measuring the two largest perpendicular dimensions. The response was graded as excellent [total disappearance], good [>50% reduction] and poor [<50% decrease]. Those patients with diffuse lymphangiomas associated predominantly with hemangiomatous malformations, mediastinal, spinal or retroperitoneal extensions, visceral lymphangiomas, those with infections were excluded from the study. Statistical analysis used: None applicable. Results: The reduction in the size of the mass usually took between two weeks to ten months. The average duration of follow up has been ten months. A significant response was seen in 8 out of the fifteen [53.33%] patients. 5 patients [33.33%] patients showed a good response to therapy and achieved >50% reduction in the size of their swellings. 2 patients [13.33%] showed a poor response to therapy and achieved less than 50% reduction in the size of the swelling. Complications of the therapy were few and far between. 2 patients developed fever after injection, one patients reported a transient increase in size of swelling, 2 patients have developed discoloration of the overlying skin and are currently being followed up for final outcome. None of the patients developed leucopenia or leukocytosis. All of the complications were managed with conservatively. Patients are on long term follow up to evaluate long term effects, if any.